Validation of the Brazilian version of the processes of change questionnaire in weight management in adults with overweight and obesity in Brazil - Quênia de Carvalho; Paola Rampelotto Ziani; Bruno Braga Montezano; Jeferson Ferraz Goularte; Adriane R Rosa (Diabetology & Metabolic Syndrome)
Abstract Background In Brazil, 57.5% of men and 62.6% of women are considered overweight, highlighting obesity as a public health issue. Obesity increases the risk of various chronic diseases, and most people struggle to maintain weight loss in the long term. The Transtheoretical Model is an approach that considers readiness for behavioral change, and questionnaires like the Process of Change Questionnaire (P-Weight), and the Stages of Change Questionnaire (S-Weight) have been developed to assess these changes in weight management. This study aims to analyze the adapted version of the P-Weight in Brazil, relate stages and processes of change, and investigate its correlation with external measures related to eating disorders. Methods A total of 656 adults participated in the study, including people in weight loss treatment and people from the general community. All participants responded to the P-Weight), the S-Weight, and the Eating Attitudes Test (EAT-26), which assesses the risk of eating disorders used as a measure of external validity. Socio-demographic variables were also investigated. Results The 33-item P-weight questionnaire showed satisfactory psychometric properties with high internal consistency (Cronbach’s alpha = 0.959). Exploratory and confirmatory factor analyses revealed a 4-factor model similar to the original Spanish version of P-Weight with a slight rearrangement of the items (KMO = 0.92, df (528, n = 328) = 8,401.015; p < 0.0001). We found significant associations between processes and stages of change (p < 0.001) and a moderate correlation between the four subscales of P-weight and EAT-26 (p < 0.001). Finally, the mean score of P-Weight was higher in the clinical sample compared to the general community, suggesting the sensitivity to discriminate cases and controls (p < 0.001). Conclusion This study showed the validity and reliability of the Brazilian version of the P-Weight scale. Therefore, the P-Weight is readily available to help professionals employ precision interventions for weight loss considering the patient’s motivational stage in combination with their individual use of the cognitive processes of change.